A viral RNA silencing suppressor interferes with abscisic acid‐mediated signalling and induces drought tolerance in Arabidopsis thaliana. (22nd October 2012) - Westwood, Jack H.; Mccann, Lucy; Naish, Matthew; Dixon, Heather; Murphy, Alex M.; Stancombe, Matthew A.; Bennett, Mark H.; Powell, Glen; Webb, Alex A. R.; Carr, John P.
Summary Cucumber mosaic virus (CMV) encodes the 2b protein, which plays a role in local and systemic virus movement, symptom induction and suppression of RNA silencing. It also disrupts signalling regulated by salicylic acid and jasmonic acid. CMV induced an increase in tolerance to drought in Arabidopsis thaliana. This was caused by the 2b protein, as transgenic plants expressing this viral factor showed increased drought tolerance, but plants infected with CMVΔ2b, a viral mutant lacking the 2b gene, did not. The silencing effector ARGONAUTE1 (AGO1) controls a microRNA‐mediated drought tolerance mechanism and, in this study, we noted that plants (dcl2/3/4 triple mutants) lacking functional short‐interfering RNA‐mediated silencing were also drought tolerant. However, drought tolerance engendered by CMV may be independent of the silencing suppressor activity of the 2b protein. Although CMV infection did not alter the accumulation of the drought response hormone abscisic acid (ABA), 2b‐transgenic and ago1‐mutant seeds were hypersensitive to ABA‐mediated inhibition of germination. However, the induction of ABA‐regulated genes in 2b‐transgenic and CMV‐infected plants was inhibited more strongly than in ago1‐mutant plants. The virus engenders drought tolerance by altering the characteristics of the roots and not of the aerial tissues as, compared with the leaves of silencing mutants, leaves excised from CMV‐infected or 2b‐transgenic plants showed greater stomatal permeability and lost water more rapidly. This further indicates that CMV‐induced drought tolerance is not mediated via a change in the silencing‐regulated drought response mechanism. Under natural conditions, virus‐induced drought tolerance may serve viruses by aiding susceptible hosts to survive periods of environmental stress.